Democratic vision of education: three scholars impacting the debates on vision of schooling - Mohamed Razali, Abu Bakar (Malaysia Association of Research and Education for Educators, 2017)
In the field of education, the debates on the purpose or vision of schooling are always engaged by educational scholars with strong passion and visionary views—provoking thoughts on educational objectives and changing instructional practices and concepts of learning. Among many, three of the main scholars in the debates on vision of schooling are John Dewey, Paolo Freire, and Lisa Delpit —whose works are always referred to and revered by those in the educational setting. The similarity that these scholars have is their democratic vision of education, i.e., the concepts of democracy in education, social justice, and equality. Their works have been referred to and argued for (and against) since their revelation up to now. Such as their impact, this article is a modest celebration of the lived realities of their ideas and further possibilities for their vision of democratic education. Many times educational debates in the purpose of schooling are not followed through or acted upon in educational policies, curricula, or instructional practices; however, they still impact the way people perceive and discuss about the purpose of education and vision of schooling—hence the future direction of education. As such, the impact the author is referring to is not in the actions taken upon such ideas (i.e., change of educational policies or reforms), but the ways in which scholars and reformers talk about and view education when debating about educational reform, instruction, curriculum, and ultimately the purpose of schooling. In addition, the focus on democratic vision of education promoted by these three scholars is important because the idea of democratic education is the essence to, and sustenance for, a democratic nation whose citizens are active and contributive to the society. In this conceptual paper, the author will briefly describe the essence of their ideas on the vision of schooling, the impact these three scholars have on debates within the education field, and tie the similarities in their ideas for a democratic vision of education.